1982
DOI: 10.1002/jlac.198219820702
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and some reactions of bis(thioacyl) sulfides

Abstract: Reaction of dithioic acids with dicyclohexylcarbodiimide has been found to give the corresponding bis(thioacy1) sulfides 1 in good yield, which are very useful thioacylating reagents under mild reaction conditions. Most of the aromatic thioanhydrides (1, R = aromatic) are fairly stable green crystals at room temperature, but the aliphatic ones (1, R = aliphatic) are unstable purple oils which dimerize at room temperature to give the dithietanes 5. The reactions with nucleophiles are discussed. Darstellung und … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The spectroscopic data and physical properties were in good agreement with that of the authentic sample which was prepared from the condensation reaction of the corresponding carbodithioic acid with dicyclohexylcarbodiimide 3b…”
Section: Methodssupporting
confidence: 72%
“…The spectroscopic data and physical properties were in good agreement with that of the authentic sample which was prepared from the condensation reaction of the corresponding carbodithioic acid with dicyclohexylcarbodiimide 3b…”
Section: Methodssupporting
confidence: 72%
“…This reaction occurs with a large evolution of H 2 S and the formation of the dithiethane, (I), as shown in the reaction scheme. A similar compound was obtained by reaction of the same dithioacid with dicyclohexylcarbodiimide (Kato et al, 1982). The crystal structure determination was undertaken to establish the conformation of the reaction product, (I), and to understand the process of its formation.…”
Section: Crystal Datamentioning
confidence: 99%
“…Kato [4] found that aliphatic thioanhydrides (1, R ‫ס‬ aliphatic, see Scheme 1) are highly unstable, whereas aromatic ones (1, R ‫ס‬ aromatic) are fairly stable. Cava [5][6][7] reported the first cyclic trithioanhydride, trithio-1,8-naphthalic anhydride (3, , and he found that 3 is very stable.…”
Section: Introductionmentioning
confidence: 98%